2014
DOI: 10.1007/s40471-014-0018-0
|View full text |Cite
|
Sign up to set email alerts
|

Breast Density and Breast Cancer Risk: Understanding of Biology and Risk

Abstract: Mammographic density is a strong risk factor for breast cancer, independent of other known risk factors. While a number of hypotheses have been proposed, the biological mechanisms underlying the association between mammographic density and breast cancer remain, however, largely unknown. Understanding these mechanisms may help identify opportunities to reduce mammographic density and ultimately breast cancer risk. We review three major areas of research that may help us better understand the biologic underpinni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Recent genetic studies have identified certain single nucleotide polymorphisms (SNPs) with overlapping effects on both BC risk and MD, suggesting that the BC risk conferred by these loci is at least partly mediated through their effects on MD [ 60 ]. Polymorphisms of genes involved in epidermal growth factor (EGF), ER and insulin-like growth factor 1 (IGF1) signalling, cell proliferation, and migration are included [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genetic studies have identified certain single nucleotide polymorphisms (SNPs) with overlapping effects on both BC risk and MD, suggesting that the BC risk conferred by these loci is at least partly mediated through their effects on MD [ 60 ]. Polymorphisms of genes involved in epidermal growth factor (EGF), ER and insulin-like growth factor 1 (IGF1) signalling, cell proliferation, and migration are included [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering mammographically dense tissue from the perspective of whole tissue cellular interactions, the influence of MD on breast cells at risk, roles of stromal cells that appear to confer risk, and adipose cells that may confer protection are key questions [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our study is among the first to comprehensively explore associations of absolute NDA with breast tumor characteristics and, to our knowledge, is the largest to date. Current hypotheses to explain associations between increased MD and breast cancer risk have been reviewed recently (29) and include the higher amount of fibroglandular tissue “at risk” of transformation into cancer (30) and the increased epithelial and fibroblast cellular activity and interaction between stroma and epithelium in dense tissue (31, 32) as well as hormonal mechanisms, including the influence of sex steroid hormones and growth factors on density and breast cancer risk (33). Evaluating associations by tumor characteristics can provide insight into these hypothesized mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Texture measures also correlate with breast cancer [9]. Although investigated for many years, the connections between breast density and the underlying biological processes are not well understood [15]. Identifying other metrics with defined spatial scales related to breast cancer could be useful for informing future studies designed to understand the related biological processes with breast structure, in addition to risk prediction purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of breast density research is often to determine an automated metric that is optimal for predicting breast cancer risk or that replicates generally, noting these may not be mutually exclusive. Although investigated for many years, the connections between breast density and the underlying biological processes are not well understood [18]. At this time, we are investigating univariate measures that can be interpreted.…”
Section: Introductionmentioning
confidence: 99%